Enhancing breast milk production with Domperidone in mothers of preterm neonates (EMPOWER trial) - Asztalos Elizabeth V; Campbell-Yeo Marsha; daSilva Orlando P; Kiss Alex; Knoppert David C; Ito Shinya (BMC, 2012)
Abstract Background The use of mother's own breast milk during initial hospitalization has a positive impact not only in reducing potential serious neonatal morbidities but also contribute to improvements in neurodevelopmental outcomes. Mothers of very preterm infants struggle to maintain a supply of breast milk during their infants' prolonged hospitalization. Galactogogues are medications that induce lactation by exerting its effects through oxytocin or prolactin enhancement. Domperidone is a potent dopamine D2 receptor antagonist which stimulates the release of prolactin. Small trials have established its ability in enhancing breast milk production. EMPOWER was designed to determine the safety and efficacy of domperidone in mothers experiencing an inadequate milk supply. Methods/design EMPOWER is a multicenter, double masked, randomized controlled phase-II trial to evaluate the safety and effectiveness of domperidone in those mothers identified as having difficulty in breast milk production. Eligible mothers will be randomized to one of two allocated groups: Group A: domperidone 10 mg orally three times daily for 28 days; and Group B: identical placebo 10 mg orally three times daily for 14 days followed by domperidone 10 mg orally three times daily for 14 days. The primary outcome will be determined at the completion of the first 2-week period; the second 2-week period will facilitate answering the secondary questions regarding timing and duration of treatment. To detect an estimated 30% change between the two groups (from 40% to 28%, corresponding to an odds ratio of 0.6), a total sample size of 488 mothers would be required at 80% power and alpha = 0.05. To account for a 15% dropout, this number is increased to 560 (280 per group). The duration of the trial is expected to be 36-40 months. Discussion The use of a galactogogue often becomes the measure of choice for mothers in the presence of insufficient breast milk production, particularly when the other techniques are unsuccessful. EMPOWER is designed to provide valuable information in guiding the practices for this high-risk group of infants and mothers. The results of this trial will also inform both mothers and clinicians about the choices available to increase and maintain sufficient breast milk. Trial registration Clinical Trials.gov Identifier: NCT01512225